If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+1=2(x-10)
We move all terms to the left:
2x+1-(2(x-10))=0
We calculate terms in parentheses: -(2(x-10)), so:We get rid of parentheses
2(x-10)
We multiply parentheses
2x-20
Back to the equation:
-(2x-20)
2x-2x+20+1=0
We add all the numbers together, and all the variables
21!=0
There is no solution for this equation
| 8=x/6+9 | | -7p=-102 | | 4u-9=-29 | | -4(y+2)=4 | | h/5+37=40 | | -33=7-4v | | w/2+4=10 | | 27=6u+3u | | f/4+14=17 | | 1+5x=64+-4x | | 18.25+z=41.4 | | 3d+1=3d | | 81=12w-3w | | 2-27x2=0 | | 4x=(5x-15) | | 30=w/5+11 | | 1/2(7x-6)=6x/10 | | 4x+2-2x=8 | | 1/2(7x-6)=6x-20 | | 20=4v+v | | p=3+1/1.6666666666667 | | -3p=(-10.8) | | 2=-8(n-1+2(-1+4n) | | -3p=-10.8 | | -6(1-5x)-4(2+2x)=8 | | ×+3y-1=0 | | 9x+4=4x+6 | | -44+x=61+4x | | 4x+6(5+x)=5(x-1) | | 6n-2n=-4(n+1)-4(n+5) | | 4x−5=x+1 | | 7+5(-2x+1)=-18-4x |